Cytotoxicity and Antitumoral Activity by Apoptosis Induction of AC13: A Brominated Curcumin Analogue - Bortolozo Oliveira, Ana Beatriz [UNESP]; Adum de Matos, Renata Prandini [UNESP]; Stuqui, Bruna [UNESP]; Torrezan, Guilherme Silva [UNESP]; Polaquini, Carlos Roberto [UNESP]; Regasini, Luis Octavio [UNESP]; Calmon, Marilia de Freitas [UNESP]; Rahal, Paula [UNESP] (Wolters Kluwer Medknow Publications, 2018)
Background: Natural compounds with therapeutic potential have been explored as antitumoral agents, as curcumin (CUR), a substance which has activity against various tumor types and a tool used to improve the action of these compounds is the production of analogs. Objective: In this study, we investigated the antitumoral activity of AC13, a CUR analog. Materials and Methods: Cytotoxicity of AC13 and CUR for different cancer cell lines was analyzed by MTT assay after 24, and 48 h of exposure and caspases 3 and 7 enzymatic activity in CasKi and human spontaneously transformed immortal keratinocyte cell line cells was analyzed after 24 h of incubation with AC13 or CUR at 50 mu M. Results: It was observed significant viability loss only for CasKi cells after incubation with AC13. Hence, it was made a more detailed screening of the cytotoxicity for these cells and nontumoral cells incubated with AC13 or CUR, showing concentration-dependent decrease of cell viability. Posteriorly, AC13 induces increase in the caspases activity in both cell lines, being that for tumor cells this increase was greater than that unleashed by CUR. Conclusion: Therefore, AC13 triggers cell death by apoptosis in CasKi and shows greater effect than CUR for these tumor cells, suggesting to be a promising compound for the treatment of cancer and should be studied more thoroughly.
Keywords: Cancer; caspase; curcumin; cytotoxicity; synthetic analogs